Pembelajaran Teknologi Informasi Dan Komunikasi (TIK) Menggunakan Model Problem Based Learning Dan Sains Teknologi Masyarakat - Puspoko Ponco Ratno (LPTK IAIN Kediri, 2022)
Information and Communication Technology (ICT) learning will be easier to apply by using relevant learning models in developing students' mindsets such as Problem Based Learning (PBL) and Science, Environment, Technology, Society (SETS). This study will discuss: (1) knowing the causes of Problem Based Learning, (2) knowing the application of technology-based learning among students and society, (3) knowing the creed of processing students' thinking skills in the learning process of information technology (IT) by applying Problem Based Learning (PBL) and Science, Environment, Technology, Society (SETS) models. The sampling technique used is a quasi-experimental method. Both tests and non-tests are data collection processes carried out in this study. The tests carried out are the initial test (pretest) and the final test (posttest). From this study, obtaining results and applying the N-gain test in the experimental class obtained a value of 0.54 in the moderate category, in the control class a value of 0.31 was obtained in the moderate category. From the results of the research it can be concluded that the Problem Based Learning (PBL) model and Science, Environment, Technology, Society (SETS) in the ICT learning process, get very good and positive responses from students and have an effect on increasing students' ability to think critically